Smell, an Underrated Early Biomarker for Brain Aging - Brai, Emanuele; Hummel, Thomas; Alberi, Lavinia (Frontiers in Neuroscience, 2020)
Olfaction is in addition to touch the most ancient of our senses, developing already in the womb it decays progressively from 65 years of age with a more pronounced impairment associated with dementia. Despite its clinical relevance and testing accessibility, smell remains an overlooked biomarker, which is rarely used by neurologists in the early screening phase. In this perspective article, we outline the reasons underlying the lack of awareness for this sense. In an attempt to put the sense of smell forward as an early biomarker for pathological brain aging, we draw a comparison with vision and hearing, regarded as more relevant for general health. The perspective article wants to encourage further studies aimed at understanding the mechanisms responsible for the early smell dysfunction in individuals a decade or more before the onset of cognitive symptoms.